2012
DOI: 10.1051/jbio/2012030
|View full text |Cite
|
Sign up to set email alerts
|

La proline, un acide aminé multifonctionnel impliqué dans l’adaptation des plantes aux contraintes environnementales

Abstract: In addition to its role in primary metabolism as a component of proteins, proline is one of the most widely distributed compatible solutes that accumulates in plants during adverse environmental constraints and plays an important role in plant stress tolerance. Proline was proposed to act as stabilizer for proteins and macromolecular complexes, scavenger of free radicals and regulator of cellular redox potential. Intracellular proline concentration depends on a tight regulation between its biosynthesis and cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Osmotic adjustment represents one of the most important features of abiotic stress tolerance in plants, while soluble proteins, soluble sugars, proline, and other compatible solutes serve as osmoprotectants under stress conditions [57,58]. Soluble proteins and sugars also protect plant cells from dehydration and stabilize and protect the biological molecules function [59].…”
Section: Resultsmentioning
confidence: 99%
“…Osmotic adjustment represents one of the most important features of abiotic stress tolerance in plants, while soluble proteins, soluble sugars, proline, and other compatible solutes serve as osmoprotectants under stress conditions [57,58]. Soluble proteins and sugars also protect plant cells from dehydration and stabilize and protect the biological molecules function [59].…”
Section: Resultsmentioning
confidence: 99%
“…Osmotic adjustment is one of the most basic characteristics of plant salt tolerance, while proline is the most widely distributed compatible penetrant [ 33 , 34 ]. Under salt stress, we measured the proline content of transgenic lines and the WT in order to understand the osmoregulation ability of transgenic plants ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…Although this review emphasizes cancer in humans, the reader should be aware of the numerous publications on proline metabolism in plants (62, 108), prokaryotes (87), insects (28), and protozoans (42). Recent reviews have shown that the proline-dependent mechanisms may be universal in the biome (5, 46).…”
Section: New Discoveries In Proline Metabolismmentioning
confidence: 99%